INDUSTRIAL REVOLUTION 5.0: DEVELOPMENT DESIGN OF TRANSACTIONS AND FINANCIAL ACCOUNTING SYSTEMS - Rina Destiana; Agus Prasetyo, Camelia Putrini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Industry 5.0 is the latest phase in industrial evolution that combines advanced technology with a human touch to create added value. Financial transaction models in the context of Industry 5.0 must be able to integrate digital technology, artificial intelligence and data analysis with humanitarian elements, such as ethics and sustainability. The Industrial Revolution 5.0 also provides opportunities for the development of financial accounting systems that can react and adjust more quickly to changes in the working environment. A more adaptive financial accounting system can integrate data from various sources, including advanced technologies such as AI and IoT, to provide more accurate and real-time information for business decision making. However, it should be remembered that the Industrial Revolution 5.0 is currently in the stages of discussion and development, so the implementation and design of developments in transactions and financial accounting systems in this context are still developing and may vary in each industry and company. The Industrial Revolution 5.0 brings changes in the development of transactions and financial accounting systems by integrating cutting-edge technologies with human creativity and experience, such robots, IoT, and AI. This can increase efficiency, flexibility and sustainability.